Risk Assessment of Petrol Filling Stations in a Metropolitical City of Kaduna State, Nigeria - Laminu S. Kuburi; Umar Umar; Ayodeji Nathaniel Oyedeji (SINERGI, 2023)
With both their high-risk and high-profit nature, Petroleum filling stations have become a significant subject in risk estimation and assessment studies. Some of the risks associated with this organization include compliance with laid-down standards by monitoring bodies. This study aims to carry out a risk assessment of petroleum filling stations in Kaduna Metropolis, Nigeria. This involved assessing the level of compliance to laid-down standards on environmental conditions and equipment and assessing the awareness of attendants in these petroleum filling stations to the possible risks in their working environment. The design methodology employed for this study was the use of self-administered questionnaires. The study result showed that the respondents were of the perspective that they are exposed to hazards in the petrol filling station. However, risks such as sleeping disorders, memory loss, cancer, etc., due to long-term exposure to hazardous petroleum substances seem to have lots of uncertainty from the attendants.